A SYSTEMATIC REVIEW ON COMMON CRISES IN THE EVENT BUSINESS (Journal of Event, Tourism and Hospitality Studies, 2024)
While the events business significantly contributes to various sectors, its inherent instability demands extra attention. The event business is considered unstable due to its susceptibility to numerous factors, including political or social issues, changing regulations, inadequate risk management, and unforeseen circumstances. Crisis, as part of unforeseen external factors, stands out as a prominent and threatening force. This study systematically reviews common crises in the events business by synthesizing and analysing relevantresearch and scholarly articles. Through the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), a systematic review protocol, this study ended up with a content analysis of 14 academic papers focused on various event-related crises. Followed by thematic coding, the study reveals that different countries may face unique crisis situations. The study emphasizes the critical importance of quick and strategic planning for managing crises, encompassing unforeseen events like COVID-19, terroristattacks, shark incidents, and earthquakes. Effective crisis management plans are essential for event organizations to navigate future challenges and enhance resilience. Regardless of location, event planners must prioritize crisis management and resilience strategies to safeguard the benefits of the events business. This systematic review paper provides valuable insights into common crisis issues, their impacts on the event industry, essential responses to crises, and practical strategies employed by event planners. It also serves as an invaluable resource for professionals in the field.